First report of two kdr mutations L1014F/S in natural populations of triatoma pallidipennis stal and triatoma picturata usinger vectors of Chagas disease in Mexico - Dávila Barboza, Jesús Antonio; Villanueva Segura, Olga Karina; Ponce García, Gustavo; López Monroy, Beatriz; Rodiguez Sanchez, Iram P.; Flores, Adriana E. (2019)
There have been around 5,000 reported cases of Chagas disease in Mexico in recent years (2013 – 2018), and these only represent a sample of the true situation with the disease (SS 2017). Given the possible transmission of the disease by 19 species of triatomines in the country, the maintenance of the disease is facilitated given the absence of a program for the monitoring and surveillance of these vectors, the use of insecticides for other vectors, and the lack of an evaluation of triatomines regarding their susceptibility to insecticides(Salazar-Schettino et al. 2010).